Accelerator mass spectrometry for radiocarbon dating - Bronk, C; Christopher Ramsey Bronk (1987)
﻿ Accelerator mass spectrometry (AMS) has been used routinely for radiocarbon measurements for several years. During this period it has become evident neither the accuracy nor the range of the technique were as great as had originally been hoped. This thesis describes both theoretical work to understand the reasons for this and practical solutions to overcome some of the problems. The production and transport of the ions used in the measurements are found to be the most crucial stages in the process. The theories behind ion production by sputtering are discussed and applied to the specific case of carbon sputtered by caesium. Experimental evidence is also examined in relation to the theories. The phenomena of space charge and lens aberrations are discussed along with the interaction between ion beams and gas molecules in the vacuum. Computer programs for calculating phase space transformations are then described; these are designed to help investigations of the effects of space charge and aberrations on AMS measurements. Calculations using these programs are discussed in relation both to measured ion beam profiles in phase space and to the current dependent transmission of ions through the Oxford radiocarbon accelerator. Improvements have been made to this accelerator and these are discussed in the context of the calculations. There are many reasons for wishing to produce C- ions directly from carbon dioxide. The most suitable type of source for achieving this is the Middleton High Intensity Sputter Source. Experiments to evaluate the performance of such a source are described and detailed design criteria established. An ion source designed and built specifically for radiocarbon measurements using carbon dioxide is described. Experiments to evaluate its performance and investigate the underlying physical processes are discussed. The source is found to have a high efficiency enabling small samples (<100 μg of carbon) to be measured. The cross contamination is measured to be low (<0.1%) and the background currents are small; the implications of these results are discussed.